Asuhan Keperawatan Keluarga Pada Ny. N Dengan Gangguan Sistem Muskuloskeletal : Gout Arthritis Di Desa Kutayu RT 01 RW 02 Kecamatan Tonjong Kabupaten Brebes - Putri Anggun Faridzatun Nafisha; Siti Fatimah; Slamet Wijaya (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Gouty arthritis is a condition that can cause persistent symptoms of pain, swelling and burning in the joints. Normal uric acid levels in women range from 2.4 - 5.7 mg/dl, while in men it ranges from 3.4 - 7.0 mg/dl, and in children 2.8 - 4.0 mg (Health et al ., n.d, 2019).